The Rebellion of the Double in Stephenson's Dr. Jekyll and Mr.Hyde and Shelly's Frankenstein - Tawfeeq , Marwan Abdulmunem (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The duality of human nature, particularly the conflict between socially acceptable and repressed desires, has been a central theme in both psychology and literature. Freudian psychoanalytic theory, which explores the conscious and unconscious mind, provides a robust framework for understanding this duality. Specific Background: The novels Frankenstein by Mary Shelley and Dr. Jekyll and Mr. Hyde by Robert Louis Stevenson, both set in the Victorian era, epitomize the struggle between repressed desires and societal norms. These works have been studied extensively, yet there remains a need for a deeper exploration of how these repressions manifest as doppelgangers and the psychological consequences therein. Knowledge Gap: Although previous studies have addressed the concept of duality in these novels, the specific role of Freudian constructs—such as the id, ego, and super-ego—in shaping the characters' fates remains underexplored. Aims: This study aims to analyze the portrayal of repressed desires through the lens of Freud's psychoanalytic theory, focusing on how these desires lead to the creation of doppelgangers in Frankenstein and Dr. Jekyll and Mr. Hyde. Results: The analysis reveals that the protagonists' repressed desires manifest in their doubles, who ultimately overpower their creators, leading to their downfall. The study shows that the failure of the ego to mediate between the id and the super-ego results in catastrophic consequences. Novelty: This research offers a novel comparative analysis that integrates Freudian theory with literary interpretation, demonstrating how repressed unconscious desires drive the narrative and character development in these works. Implications: The findings suggest broader implications for understanding the psychological effects of repression in both literature and real-world contexts, particularly within the framework of societal expectations and individual desires. Highlights: Freudian Constructs: Id, ego, and super-ego drive character actions and outcomes. Doppelganger Analysis: Repressed desires surface through literary doubles, leading to downfall. Victorian Idealism: Conflict between societal norms and hidden ambitions creates tension. Keywords: Freudian psychoanalysis, duality, repression, doppelganger, Victorian literature